If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 10 = 2x + 46 Reorder the terms: 10 + 8x = 2x + 46 Reorder the terms: 10 + 8x = 46 + 2x Solving 10 + 8x = 46 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + 8x + -2x = 46 + 2x + -2x Combine like terms: 8x + -2x = 6x 10 + 6x = 46 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + 6x = 46 + 0 10 + 6x = 46 Add '-10' to each side of the equation. 10 + -10 + 6x = 46 + -10 Combine like terms: 10 + -10 = 0 0 + 6x = 46 + -10 6x = 46 + -10 Combine like terms: 46 + -10 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| 13-(m+n)= | | n^2=2n-3 | | (1+x+2)2= | | -18-3x=-57 | | 2+11/5x=21/5x | | 3/4+z=5/6 | | 5(x-2)+1=26 | | 2/(7+x)=3 | | y+4x=-2 | | 16=3x+9 | | q-9=-54 | | 16=x^2+6x | | 2/3x-4/7x+2 | | -4+x=14 | | w+-5=40 | | 4x^2-22x+18=-8x+4 | | 3/5x=2/7 | | 2x^2-5x=3x+10 | | 5/6=x/30 | | q+-10=-25 | | (5/6)=(x/30) | | 31x^4=x^2 | | (v+10)(v-12)=0 | | 3/7=x/21 | | x/4=7/5 | | 2x+5-9=-12 | | 2x+5-9=12 | | 7/3x+10/3x=16 | | 9+x+4= | | 8x-10=3(6-2x) | | x+4*9=2x | | 1/x+1/x=10 |